Development of Disease Suppressive Compost and Potting Mix for Control of Bacterial Wilt of Tomato - Masyitah (2004)
In Malaysia, bacterial wilt caused by Ralstonia solanacearum is considered a major factor limiting tomato production in the lowlands. Compost usage had effectively suppressed diseases. Therefore, developing and evaluating composts for suppression of bacterial wilt of tomato were carried out. Three types of composts, made from corn stalk, rice straw and tree bark, each mixed with chicken dung, were composted using the forced aeration method. Their maturity, quality and disease suppression were evaluated. in the laboratory, greenhouse and field experiments. The phytotoxicity test showed that the corn stalk and rice straw compost extracts significantly (P < 0.01) decreased germination, root length and germination index of tomato compared to control. However, the tree bark compost extract at both 10% and 30% concentrations did not affect germination, root length and germination index of tomato. 4 In plant bioassay, the corn stalk and rice straw composts significantly (P<0.01) decreased seed germination and fresh weight of tomato seedlings compared to the control. However, the tree bark compost up to 50% concentration did not affect seed germination and fresh weight of tomato. An experiment on suppression of Pythium damping off disease showed that the tree bark compost gave the highest disease suppression of 80.58% and 71.96% in tomato and Brassica sp, respectively. Greenhouse trial on suppression of bacterial wilt of tomato caused by R. solanacearum, showed that all composts significantly reduced the disease but treatment with the tree bark compost recorded significantly lowest disease severity index (1.2) and disease incidence (40%). Evaluation of potting mixes showed that the potting mix with composition of peat:sand: tree bark compost in the ratio of (5:3:2) gave the best soil physical properties and plant growth. In the greenhouse experiment, the incorporation of tree bark compost in potting mixes of peat:sand:compost in ratio of 5:3:2 added with antagonist Pa II (Pseudomonas aeruginosa) and Kts 26 (Pseudomonas putida) individually, and Kt8 (Pseudomonas aeruginosa) + B333 (Pseudomonas aeruginosa) in combination antagonists significantly gave lower disease severity index and disease incidence of bacterial wilt of tomato compared to other antagonists tested. In the field trial using the three antagonists showed that the tree bark compost potting mix added with Kt8 + B333 in combination gave 57% reduction of bacterial wilt disease of tomato which was better compared to Pa II (50%) and Kts 26 (50%) individually.